Mengenal Ehabla, Puisi Lisan Sentani, Papua - Wigati Yektiningtyas Modouw (Balai Bahasa Provinsi Papua, 2019)
Ehabla is one of Sentani oral poetry that is spontaneously sung in the singing spot. The research was conduted in Sentani Papua in 2004-2008. The data were taken directly from the field through recording. The data were then transcribed, translated into Indonesian and analyzed. Dealing to the limited space, the paper will only serve some of the data used to illustrate how usually ehabla is sung. Through the research, it is found that ehabla is rarely heard. Not many people, especially people who live near Jayapura city and young generation, know the song. It is predicted that, without preservation and socialization, ehabla will extinct in some years. The research found the composition, formula, theme, and notation of ehabla that is discussed in the paper. Hopefully, this writing can help and motivate young singers (generation) to learn ehabla.